2009
DOI: 10.1016/j.scaman.2008.11.008
|View full text |Cite
|
Sign up to set email alerts
|

CSR and the legitimacy of business in transition economies: The case of Russia

Abstract: In this paper we attempt to investigate the attitudes towards their perceived social responsibility on the part of the executives of a sample of medium and large Russian companies. Our empirical study is based on an original survey of executive managers of 500 industrial enterprises in almost all regions of Russia. We designed our questionnaire using as a starting point some important conclusions made by theorists who analysed the development of CSR in mature capitalist economies. Our objective was to probe wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 36 publications
2
99
1
1
Order By: Relevance
“…CSR theories, concepts and ideas primarily originate from market economy countries with relatively strong institutional environments in which regulation is efficient and fairly enforced. Yet in a number of emerging economies and developing countries with weak institutional environments underlined by arbitrary enforcement of law, bureaucratic inconsistency, insecurity of property rights and corruption, corporate social responsibility may get a very different twist (Kuznetsov et al, 2009;Jamali et al, 2007).…”
Section: Context Dependency Of Csrmentioning
confidence: 99%
“…CSR theories, concepts and ideas primarily originate from market economy countries with relatively strong institutional environments in which regulation is efficient and fairly enforced. Yet in a number of emerging economies and developing countries with weak institutional environments underlined by arbitrary enforcement of law, bureaucratic inconsistency, insecurity of property rights and corruption, corporate social responsibility may get a very different twist (Kuznetsov et al, 2009;Jamali et al, 2007).…”
Section: Context Dependency Of Csrmentioning
confidence: 99%
“…Conversely, Kuznetsov, Kuznetsova & Warren (2009) use a self-reporting quantitative survey of Russian firms to conclude that Russian managers do not view CSR as a legitimate activity for business, whilst Preuss & Barkemeyer (2011) use company reports to indicate that a significant proportion of large Russian firms do include CSR information within their external reporting, although often only in the English language.…”
mentioning
confidence: 99%
“…Accordingly, government and business actors appear to be tightly intertwined and following a joint agenda. Interestingly, this seems somewhat at odds with evidence from a recent research study that found businesses in Russia are keen to distance themselves from the state (Kuznetsov et al 2009) following the economic and political changes in the country since the early 1990s.…”
Section: Methodsmentioning
confidence: 96%
“…Actors can be selective about which regulations they employ to defend their positions, and not all actors regard all state actions and interests as legitimate. Available evidence suggest that governments in developing economies often lack coherent and accepted regulatory frameworks that can serve as stable and powerful legitimacy benchmarks (Ö zcan 2006;Kuznetsov et al 2009). In this way, the power balance between social actors is not only unequal but also unstable.…”
Section: The Relational Governance Framework Augmented and Adaptedmentioning
confidence: 99%
See 1 more Smart Citation